Combining anti‐IgM and IgG immunoassays for comprehensive chikungunya virus diagnostic testing. (26th August 2019) - Mendoza, Emelissa J.; Robinson, Alyssia; Dimitrova, Kristina; Mueller, Nicole; Holloway, Kimberly; Makowski, Kai; Wood, Heidi
Abstract: Chikungunya virus (CHIKV) is a mosquito‐borne pathogen that causes CHIKV fever. Definitive diagnosis is crucial for patients experiencing symptoms similar to other arboviral diseases because they can vary in clinical consequences. An increasing number of patients experience long‐term rheumatic effects of CHIKV infection, but these cases may not be optimally detected by molecular assays and anti‐CHIKV IgM ELISAs (M‐ELISAs) used for confirmation and screening, respectively. The subsequent confirmatory serological test, the plaque reduction neutralization test (PRNT), is laborious and time‐consuming. In this study, we evaluated a new diagnostic algorithm in which the M‐ELISA is conducted in parallel with an anti‐CHIKV IgG ELISA (G‐ELISA) and observed that the Euroimmun M‐ELISA combined with the Euroimmun G‐ELISA or the Abcam G‐ELISA exhibited excellent sensitivity and specificity for CHIKV. The combinations demonstrated perfect and near perfect inter‐rater agreement with the PRNT, respectively, suggesting their potential to be used as alternatives to the confirmatory serological PRNT assay for CHIKV.